The Myopia of Web Services Management what's in your architecture?. - Boonin, Sam (SOA webservices journal.)
Rather than taking a myopic Web services management approach to realizing the promise of shared services, enterprise architects should focus on building the architecture that controls chaos and enables sharing and reuse.